A highly uniform CuO@SiO2 porous sphere with improved electrochemical sensing performance for the accurate determination of vanillin in food samples. (December 2021) - Venkadesh, A.; Mathiyarasu, J.; Radhakrishnan, S.
Abstract: A porous sphere of CuO@SiO2 was obtained by simple calcination of the copper silicate (CuSiO3 ) sphere. The formation of the porous sphere was studied in detail with the support of various physical characterization techniques. The CuO@SiO2 was coated on an electrode surface where it demonstrates high catalytic activity for the electro-oxidation of vanillin in phosphate buffer solution (PBS; pH 7.0). The modified electrode has good surface adsorption (1.861 × 10 −10  mol cm −2 ) and rate constant (2.866 × 10 5  cm 3  mol −1  s −1 ) characteristics for vanillin detection. The CuO@SiO2 -modified surface exhibited good linear range (0.05 μM–1.2 μM and 6.2 to 111.2 μM), detection limit (53 nM), sensitivity (2.88 μA μM −1  cm −2 ), selectivity, stability, and reproducibility. The CuO@SiO2 -modified electrode was further examined for the determination of vanillin in real samples including biscuits and chocolates with satisfactory recoveries. Highlights: The vanillin sensing platform was designed using porous CuO@SiO2 . The CuO@SiO2 sphere was prepared by a simple, low-cost, and eco-friendly approach. The CuO@SiO2 material showed good electrochemical properties. The CuO@SiO2 based vanillin sensor demonstrated a good analytical performance.